The exceptional power of the dead in Heid E. Erdrich's "National monuments" - Madsen, Deborah Lea (State University of New York Press, 2021)
American exceptionalism, the idea that the US nation was created by God's will to be a model to the world, works in large part through the territorial narrative of “Manifest Destiny,” which claims a divine mission to occupy the entire American continent. Of course, this narrative must disavow the violence with which the settler nation occupies the land on which are constructed the social, political, and cultural institutions of the US. Whether the bloodshed of the War of Independence, the brutality of “King Philip's” (Metacomet's) War of the 1670s, the violence of the so-called “Indian Wars” that coincided with the relentless westward expansion of the US throughout the nineteenth century, or the ongoing conflict between Indigenous nations and the settler nation that is the US, this history of devastation is disavowed by the rhetoric of American exceptionalism. But beneath this narrativized history there lies a trail of dead human bodies, lifeless bones, that refuse the disavowal of their stories. The history of settler violence in the US is signified by the human remains – both Indigenous and settler – that are the primary product of this violent process of colonial “nation-building.” What sets apart the corpses of settlers and Natives who died in the same conflict? Most fundamentally, the answer to this question lies in the disposal of the corporeal remains that endure to tell the story of their deaths. While the heroic remains of US soldiers are feted and memorialized, the remains of Indigenous people are shipped to hospitals, museums, research collections – all institutions within the structure of the US federal government. Indigenous human remains become wards of the state, hostages to the claim of Manifest Destiny. The poems in Heid Erdrich's "National Monuments" challenge the exceptionalist history of America, relocating the US national narrative in the discursive environment of Anishinaabe storying.